Hypoxia-tropic delivery of nanozymes targeting transferrin receptor 1 for nasopharyngeal carcinoma radiotherapy sensitization - Ruofei Zhang; Yanfang Shen; Xiaoying Zhou; Jianru Li; Hanqing Zhao; Zixia Zhang; Jun Zhao; Hongjun Jin; Shuanshuan Guo; Hui Ding; Guohui Nie; Zhe Zhang; et al. (Nature Communications)
Abstract Nasopharyngeal carcinoma (NPC), a malignancy highly prevalent in East and Southeast Asia, is primarily treated with radiotherapy (RT). However, hypoxia-induced radioresistance presents a significant challenge. Nanozymes, nanomaterials with catalase-like activity, have emerged as a promising strategy for radiosensitization by converting elevated hydrogen peroxide in the tumor microenvironment into oxygen. Despite their potential, effectively targeting hypoxic lesions has been difficult. Here, we identify transferrin receptor 1 (TfR1) as an upregulated target in NPC, with its expression levels positively correlated with hypoxia. Human heavy-chain ferritin, a specific ligand of TfR1, selectively recognizes hypoxic NPC lesions in preclinical models. Based on these findings, we design a hypoxia-targeted nanozyme by loading platinum nanoparticles into ferritin. This nanozyme exhibits enhanced catalase-like activity and effectively alleviates tumor hypoxia in NPC xenografts. When combined with RT, a single injection of the nanozyme significantly inhibits tumor growth and prolongs mouse survival, outperforming sodium glycididazole, a clinically used radiosensitizer. In summary, our findings highlight TfR1 as an accessible cell surface target in hypoxic NPC lesions. The nanozyme targeting TfR1 holds promise for enhancing the therapeutic effectiveness of RT in NPC through an in situ oxygen-generation mechanism.